Biochar performance for preventing cadmium and arsenic accumulation, and the health risks associated with mustard (Brassica juncea) grown in co-contaminated soils - Yili Zang; Min Wang; M.J.I. Shohag; Lingli Lu; Tieguang He; Changjun Liao; Zengyu Zhang; Jiancheng Chen; Xiaoshuang You; Yihan Zhao; Yanyan Wei; Shengke Tian (Ecotoxicology and Environmental Safety, 2023)
Cadmium (Cd) and arsenic (As) in co-contaminated soil can enter the human body harming health via the food chain, such as vegetables. Biochar derived from waste has been used to reduce heavy metal uptake by plant, but long-term effects of biochar under Cd and As co-contaminated soil needs to be investigated. A following mustard (Brassica juncea) was grown on co-contaminated soil amended with different raw materials of biochar including biochars pyrolyzed by lignite coal (LCB), rice straw (RSB), silkworm excrement (SEB), and sugar refinery sludge (SSB). The results showed that compared to the control, Cd and As contents of mustard shoot in SSB treatment decreased by 45–49% and 19–37% in two growing seasons, respectively, which was the most effective among 4 biochars. This probably due to SSB owns more abundant Fe-O functional groups. Biochar also altered the microbial community composition, specifically SSB increased proteobacteria abundance by 50% and 80% in the first and second growing seasons, thereby promoted the simultaneous immobilization of Cd and As in soils which may reduce the potential risks to humans. In summary, considering the long-term effects and security of SSB application on mustard, not only is it an effective waste recycle option, but it should also be promoted as a promising approach for safe vegetable production in Cd and As co-contaminated soils.